OPTIMASI PARAMETER PROSES WAX PATTERN INJECTION TERHADAP PRODUK CASING PUMP VS 2/4/6 X MENGGUNAKAN METODE RESPONSE SURFACE - Kholish Adilah Damayanti; Farizi Rachman; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Wax injection machining is the only technique to produce many ideal products in large volumes, which is the most common method in the investment casting process. One of the products that has the highest number of orders in metal casting companies using investment casting techniques is the pump casing VS 2/4/6 X product. The VS 2/4/6 X pump casing product consists of 4 components, each of which is injected into a different mold and eventually assembled into a product. Some of the problems encountered in the wax pattern injection results are dimensional accuracy and product defects. Some parameters that will be analyzed for dimensional accuracy and product defects are injection time, injection pressure, and holding time. This research uses response surface method with 15 run orders with 3 replications and applies Box-Behnken Design for research experimental design and ANOVA to analyze the data. Based on the analysis results. It was found that the optimal parameter combination is the value of injection time of 80 seconds, injection pressure of 35 bar, and holding time of 50 seconds. From this configuration, the dimensional accuracy value is 146.230 mm.